Waqf Literacy: A Systematic Literature Review - Nashr Akbar; Salina Kassim; Fahd Mohammed Obad Al-Shaghdari; Irfan Syauqi Beik (Department of Islamic Economics, IPB University, 2026)
This paper aims to provide a systematic literature review of waqf literacy. The studies on the waqf literacy were initiated in 2015 and it showed growing trends in 2021 onward. The significant increase of scholars’ awareness toward waqf literacy issue could be triggered by publication of Indonesian waqf literacy index by Indonesian Waqf Board in 2020. There are 66 documents published between 2015 - May 2024 in total. The documents are extracted from the Dimension database and the Scopus database. The analysis found that most of documents discussed the contribution of waqf literacy toward waqf collection. Many empirical studies have proved the positive relationship between waqf literacy and waqf collection (at least at the level of intention). Those papers urge waqf stakeholders to collectively increase the level of waqf literacy. Several studies have attempted to elaborate further strategies that could be adopted by the stakeholders. To conclude, not many scholars have put their attentions toward waqf literacy. Despite of its important, attention to waqf literacy is still minimum compared to other area of waqf, zakat literacy and even to the Islamic financial literacy. More studies are needed. There are several topics in waqf literacy that could be addressed in the future, such as examining the determinants of waqf literacy, perfecting the measurement of waqf literacy index, and offering more ideas on how to increase waqf literacy.